Surgical palliative care - Mosenthal, Anne C.; Dunn, Geoffrey P. (New York : Oxford University Press, 2019)
This volume on surgical palliative care guides readers through the core palliative skills and knowledge needed to deliver high value care for patients with life-limiting, critical, and terminal illness under surgical care.'Surgical Palliative Care' is an ideal resource for surgeons, surgical nurses, intensivists, and other practitioners who wish to learn more about integrating palliative care into the surgical field.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 1, 2019).
Keywords: Palliative treatment; Surgery